2020
DOI: 10.14440/jbm.2020.324
|View full text |Cite
|
Sign up to set email alerts
|

A system for the high-throughput analysis of acute thermal avoidance and adaptation in C. elegans

Abstract: Nociception and its plasticity are essential biological processes controlling adaptive behavioral responses in animals. These processes are also linked to different pain conditions in human and have received considerable attention, notably via studies in rodent models and the use of heat-evoked withdrawal behavior assays as a readout of unpleasant experience. More recently, invertebrates have also emerged as useful complementary models, with their own set of advantages, including their amenability to genetic m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 38 publications
2
10
0
Order By: Relevance
“…First, we evaluate heat-evoked reversals in wild type and cmk-1 mutants. Similar to previous findings 50 , loss of cmk-1 in cmk-1(ok287) mutants increased the animal responsiveness to acute stimuli (Fig. 5B).…”
Section: Cmk-1 Nls 71-78 and Nes 288-294 Elements Are Essential For Thermal Avoidance Responsiveness And Plasticitysupporting
confidence: 91%
See 2 more Smart Citations
“…First, we evaluate heat-evoked reversals in wild type and cmk-1 mutants. Similar to previous findings 50 , loss of cmk-1 in cmk-1(ok287) mutants increased the animal responsiveness to acute stimuli (Fig. 5B).…”
Section: Cmk-1 Nls 71-78 and Nes 288-294 Elements Are Essential For Thermal Avoidance Responsiveness And Plasticitysupporting
confidence: 91%
“…The first pulse was at heating power of 0.3 W/m 2 and the second one at a heating power of 0.6 W/m 2 . We used a previously described system for heat delivery, worm movie recording and reversal flagging 20 . The genotype effects were the same at both heating power levels, and the data were pooled for the reversal analysis.…”
Section: Behavioral Assaysmentioning
confidence: 99%
See 1 more Smart Citation
“…2013 ; Byrne Rodgers and Ryu 2020 ). Repeated whole-animal noxious heat stimulations (delivered every 20 s) cause the worm responsiveness to progressively decline over a 1-hour period ( Lia and Glauser 2020 ). This habituation-like adaptation phenomenon represents a simple nociceptive plasticity experimental paradigm.…”
Section: Introductionmentioning
confidence: 99%
“…The main goal of this study was to evaluate the potential of using C. elegans thermal nociception as an experimental system to study if and how recently identified human pain-associated genes control nociception and its plasticity in vivo. To that end, we identified worm orthologs for a set of candidate human pain genes and tested 109 available worm mutant lines by quantifying thermal avoidance using a recently established semi-automated, computer-assisted system ( Lia and Glauser 2020 ). We focused on three main phenotypic aspects: (1) the spontaneous reversal rate, assessed in the absence of heat stimuli, (2) the thermal sensitivity of the worms, assessed with a series of heat stimuli of raising intensities, and (3) the nociceptive plasticity, assessed by comparing the responsiveness of naïve (unstimulated) animals and adapted animals (submitted to a train of repeated heat stimulation).…”
Section: Introductionmentioning
confidence: 99%